GRAECO-LATIN SQUARE DESIGN ON THE OPTIMIZATION OF CROP NUTRIENT BY APPLICATION OF FERTILIZER TO THE SOIL - Abubakar , Muhammad Auwal; Nweze, N O; Oseni , Halimat Olajumoke; Osagie, Adenomom Monday (Economics and Statistics Research Journal (ESRJ), 2025)
This study investigates the optimization of crop nutrient application using the Graeco-Latin Square Design (GLSD), with a focus on four different varieties of guinea corn cultivated on Phanadam Farm in Bwari, Abuja, over four harvest seasons (2020–2023). The research assessed the effects of crop variety, soil type, cropping system, and fertilizer type on crop yield. Employing a GLSD of order 4, the design efficiently controlled for three sources of variability, allowing for a robust analysis of the four treatment factors. Data were obtained from secondary sources and analyzed using Analysis of Variance (ANOVA). Results indicated that there were no statistically significant differences in yield attributable to crop variety, soil type, cropping system, or fertilizer type, as the F-calculated values were consistently lower than the F-tabulated value of 9.28. These findings suggest that although these factors may intuitively affect yield, uniform application of fertilizers can standardize yield across different conditions. The study recommends the consistent use of fertilizers in guinea corn production, regardless of variety or environmental factors, to enhance agricultural productivity